Fragmentation of Ammonium Nitrate Particles under Thermal Cycling. Issue 3 (30th January 2018) - Maggi, Filippo; Garg, Priya
Abstract: Ammonium nitrate finds application in explosives and chlorine‐free slow‐burning propellants. Different phases are known for this ammonium salt, each of them featured by peculiar bulk densities. As a consequence, the variation of storage temperature induces processes of expansion‐contraction in the crystals, unless specific stabilization is performed. In this paper, a batch of raw ammonium nitrate particles has been thermally cycled between −30 °C to +60 °C and analyzed. Microscopic observations, particle size measurement, and X‐ray microtomography showed that the particles undergo a progressive fragmentation process, with opening of internal cracks and voids. The tested material halved its mass‐mean diameter after five thermal cycles. As a term of comparison, a phase‐stabilized ammonium nitrate batch was tested under the same conditions, showing no effect. Abstract :